Automatic Detection of Irrelevant Comments in an Electronic Meeting (INTERNATIONAL JOURNAL OF MANAGEMENT & INFORMATION TECHNOLOGY, 2017)
Groups exchanging ideas in electronic meetings often generate irrelevant or off-topic comments that can detract from the conversation. Here, we describe a system that seeks to identify this immaterial text using previously identified keywords. Results of an experiment with the system show that group members believe meetings do have irrelevant comments that waste time, but participants often enjoy them. The system achieved an F measure of 42.3% for recall and precision, and further research is necessary to determine if this is sufficient or what can be done to improve this score.